POLITENESS STRATEGY OF JAVANESE IN WELCOMING GUEST USED BY JAVANESE PEOPLE WHO ARE LIVING IN MALANG - SETIARA, SERA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Key word: Politeness Strategies, Contexts, Javanese, Javanese people Javanese has differences of speaking local language refer to dialect. There are three levels speech in Javanese such as: ngoko, madya, and krama. This study has two objectives, first is to identify the politeness strategies of Javanese used by Javanese people who are living in Malang when they are welcoming guests. Second one is to identify the contexts of politeness strategies of Javanese used by Javanese people who living in Malang when they are welcoming their guests, especially their Javanese utterances when they are giving a seat to the addressee. In this study, research method which is used is qualitative. Type of study is a case study to get information deeply used the subject’s observation as mutiple methods to gather data. The result from the observation shows that 12 utterences from Javanese people have different politeness when they are  welcoming their guests. The data were taken from the different age, sex, marital status, education background, occupation and utterance from Javanese dialect proposed by Kartomihadjo (1979) which used in welcoming their guest: age: 18-40 years, sex: male or female, education background: S1, occupation: entrepreneur, student, employee, utterance (Javanese) mangga pinarak (krama), monggo lenggah (madya), lungguho (ngoko) and status relationship between addreseer and addressee proposed by Holmes (1995) with categories : senior-junior, junior-senior, or friend also have more effect of politeness strategies used by addreseer to get the limitation of politeness in language use. It can be concluded, there are 7 subjects utterances used Ngoko level but 1 subject utterance used negative politeness, 3 subjects utterances used madya, 2 subjects utterances used Krama.The writer wants to give a suggestion for both the students of Study Program of English and the future researchers to analyze other politeness strategies of other languages which are almost extinct. They can use a research approach which involvepoliteness strategies in other languages to understand and cultivate sense of languagevarieties in Indonesia.